Equity Market & Islamic Finance: Innovation and Product Development - Antonio, Muhammad Syafii (Ekonomi Islam Indonesia, 2023)
The growth of the Islamic finance industry has been encouraging and it is becoming more advanced. In its early development, product offerings of Islamic finance tended to be in more traditional area such as (murabahah) financing and funding. However, as the industry matures, the trend is towards a more sophisticated and complex products and financial instruments. This paper attempts to provide a brief overview of this development, with a strong emphasis on shariah perspectives. The paper begins with reviewing the philosophy of an Islamic economy, especially its moral aspects and main objectives. Then it will show some recent global developments in the Islamic finance industry and Islamic capital markets. From this overview, it also becomes necessary to highlight a conceptual overview of the nature and process in designing Islamic finance products, followed by a close look at the progress of the Islamic equity market, especially sukuk. The paper also observes the strategic position of values and ethics in product development, specifically through a shariah governing body such as National Shariah Boad in Indonesia and Shariah Advisory Council in Malaysia. At the end the paper identifies some critical issues on the development of Islamic equity and finance products.